Microplastics and viruses in the aquatic environment: a mini review - Wang, Xiuwen; Zheng, Kaixin; Wang, Yi; Hou, Xin; He, Yike; Wang, Zhiyun; Zhang, Jiabo; Chen, Xiaochen; Liu, Xianhua (Frontiers in Microbiology, 2024)
Microplastics (MPs) have been widely found in the environment and have exerted non-negligible impacts on the environment and human health. Extensive research has shown that MPs can act as carriers for viruses and interacts with them in various ways. Whether MPs influence the persistence, transmission and infectivity of virus has attracted global concern in the context of increasing MPs contamination. This review paper provides an overview of the current state of knowledge regarding the interactions between MPs and viruses in aquatic environments. Latest progress and research trends in this field are summarized based on literature analysis. Additionally, we discuss the potential risks posed by microplastic-associated viruses to human health and the environmental safety, highlighting that MPs can affect viral transmission and infectivity through various pathways. Finally, we underscores the need for further research to address key knowledge gaps, such as elucidating synergistic effects between MPs and viruses, understanding interactions under real environmental conditions, and exploring the role of biofilms in virus-MPs interactions. This review aims to contribute to a deeper understanding on the transmission of viruses in the context of increasing MPs pollution in water, and promote actions to reduce the potential risks.